The Coordinated Voltage Control Meets Imperfect Communication System - Xu, Jiangjiao; Sun, Hongjian; Dent, Chris (Institute of Electrical and Electronics Engineers, 2016)
High penetration of Distributed Generations (DGs) will have impact on the development of power systems. Due to the uncertainty of the DG output, it becomes extremely difficult to control the system voltage profile. This paper proposes a coordinated decentralized voltage control method, together with a self-excited inverter, that can control the voltage level by reactive power injection/absorption. The time-delay introduced by communications among DGs is considered to validate the proposed control approach. Simulation results show that the coodinated control approach is sensitive to the time-delay in a 33-bus medium-voltage distribution network (MVDN).
EPrint Processing Status: Full text deposited in DRO